Discovery of quality markers of Meconopsis quintuplinervia based on an absorption-based metabolite approach and rapid quantification using polarity-switching UPLC-QQQ-MS/MS - Tian, Yifan; Liu, Yuan; Kong, Yuanlin; Li, Limin; Yang, Zhengming; Li, Wenbin; Li, Qiang; Ren, Chaoqin; Sun, Wenxia; Huang, Yanfei (Frontiers in Pharmacology, 2024)
Background: Meconopsis quintuplinervia Regel (MQ) is a traditional Chinese medicine (TCM) used for clearing liver and lung heat in Tibetan medicine for thousand years. However, the lack of quality markers that correlate with pharmacological actions and absorption in vivo limits the safety and efficacy in the clinical application and drug market. Furthermore, a universal and rapid method for the simultaneous determination of quality markers in MQ crude drug is still lacking.Purpose: In the present study, an absorption-based metabolites approach was used to discover and identify the quality markers of MQ. Then, an efficient method based on the polarity-switching ultraperformance liquid chromatography triple quadrupole mass spectrometry (UPLC-QQQ-MS/MS) technology was established to determine the quality markers.Methods: First, the absorbed compounds and metabolites were characterized using ultraperformance liquid chromatography plus Q-Exactive Orbitrap tandem mass spectrometry (UPLC-Q-Exactive Orbitrap-MS) after giving oral MQ extract to rats. Subsequently, the absorbed compounds and precursors of metabolites correlating with the hepatocyte protection activity were screened as quality markers. Finally, a polarity-switching UPLC-QQQ-MS/MS method was developed for quantitative analysis of MQ crude drug, which enable the detection of quality markers in both negative and positive ion modes in a single run. The MS 2 characteristics of target compounds were investigated to select appropriate product ions.Results: A total of 13 absorbed compounds and 30 metabolites were characterized. Among them, nine compounds, including five absorbed compounds and four precursors of metabolites intimately correlated with hepatocyte protection activity and absorption in vivo, were considered as the quality markers of MQ in the current study. The quantification of quality markers was conducted using an Acquity UPLC HSS T3 (2.1×100 mm, 1.8 μm) column, the mobile phase consisted of acetonitrile and 0.1% formic acid solution (containing 10 mmol/L ammonium acetate). The validated UPLC-QQQ-MS/MS method was successfully applied to quantify the quality markers in MQ crude drug.Our study defined the quality markers and established a universal and rapid method for the simultaneous determination of quality markers of MQ, which will be helpful for further investigation of quality evaluation of MQ in the clinical application and drug market.